1998
DOI: 10.1002/(sici)1097-0061(19980330)14:5<443::aid-yea243>3.0.co;2-l
|View full text |Cite
|
Sign up to set email alerts
|

Evolution of gene order and chromosome number inSaccharomyces,Kluyveromyces and related fungi

Abstract: The extent to which the order of genes along chromosomes is conserved between Saccharomyces cerevisiae and related species was studied by analysing data from DNA sequence databases. As expected, the extent of gene order conservation decreases with increasing evolutionary distance. About 59% of adjacent gene pairs in Kluyveromyces lactis or K. marxianus are also adjacent in S. cerevisiae, and a further 16% of Kluyveromyces neighbours can be explained in terms of the inferred ancestral gene order in Saccharomyce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

9
70
1
2

Year Published

1998
1998
2014
2014

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 111 publications
(82 citation statements)
references
References 72 publications
(131 reference statements)
9
70
1
2
Order By: Relevance
“…Dots anywhere else in the plot indicate rearrangements. Several previous studies have reported examples where K. lactis (or Kluyveromyces marxianus) has an ''ancestral'' gene order consisting of intermingled genes from parts of two different S. cerevisiae chromosomes (2,4,11,21). In a proximity plot, this intermingling creates ''minor'' diagonals of dots between the two S. cerevisiae chromosomes involved (Fig.…”
Section: Resultsmentioning
confidence: 74%
See 2 more Smart Citations
“…Dots anywhere else in the plot indicate rearrangements. Several previous studies have reported examples where K. lactis (or Kluyveromyces marxianus) has an ''ancestral'' gene order consisting of intermingled genes from parts of two different S. cerevisiae chromosomes (2,4,11,21). In a proximity plot, this intermingling creates ''minor'' diagonals of dots between the two S. cerevisiae chromosomes involved (Fig.…”
Section: Resultsmentioning
confidence: 74%
“…bayanus pair than to any other species in Génolevures. S. exiguus and S. servazzii are estimated to have 16 and 12 chromosomes, respectively (28), as compared with the basal number of 6-8 chromosomes in K. lactis, Z. rouxii, and S. kluyveri (4,6). It is therefore possible that the genome duplication occurred at the point marked with an asterisk in Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The ends of the clusters probably correspond to sites of chromosomal translocations (16,26,27). In some cases a cluster of genes in C. albicans is related to two S. cerevisiae genomic regions (blocks) that are paired by whole-genome duplication in the S. cerevisiae lineage (26), as predicted by our model (16,27). The relationships shown in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…The extent of gene order conservation among ascomycete fungi previously has been estimated by comparing the S. cerevisiae genome sequence (12) to DNA sequences from other species, using either random ''genome survey'' sequences from both ends of small clones (13)(14)(15) or existing European Molecular Biology Laboratory database sequences (16). Between Saccharomyces cerevisiae and Candida albicans, two species separated by 140 -330 million years (17,18), only one example of conserved gene order and orientation has been reported so far (STE6-UBA1; ref.…”
mentioning
confidence: 99%